Acute HIV infection detection and immediate treatment estimated to reduce transmission by 89% among men who have sex with men in Bangkok. Issue 1 (28th June 2017) - Kroon, Eugène D.M.B.; Phanuphak, Nittaya; Shattock, Andrew J.; Fletcher, James L.K.; Pinyakorn, Suteeraporn; Chomchey, Nitiya; Akapirat, Siriwat; de Souza, Mark S.; Robb, Merlin L.; Kim, Jerome H.; van Griensven, Frits; Ananworanich, Jintanat; et al.
Abstract: Introduction : Antiretroviral treatment (ART) reduces HIV transmission. Despite increased ART coverage, incidence remains high among men who have sex with men (MSM) in many places. Acute HIV infection (AHI) is characterized by high viral replication and increased infectiousness. We estimated the feasible reduction in transmission by targeting MSM with AHI for early ART. Methods : We recruited a cohort of 88 MSM with AHI in Bangkok, Thailand, who initiated ART immediately. A risk calculator based on viral load and reported behaviour, calibrated to Thai epidemiological data, was applied to estimate the number of onwards transmissions. This was compared with the expected number without early interventions. Results : Forty of the MSM were in 4th‐generation AHI stages 1 and 2 (4thG stage 1, HIV nucleic acid testing (NAT)+/4thG immunoassay (IA)‐/3rdG IA–; 4thG stage 2, NAT+/4thG IA+/3rdG IA–) while 48 tested positive on third‐generation IA but had negative or indeterminate western blot (4thG stage 3). Mean plasma HIV RNA was 5.62 log 10 copies/ml. Any condomless sex in the four months preceding the study was reported by 83.7%, but decreased to 21.2% by 24 weeks on ART. After ART, 48/88 (54.6%) attained HIV RNA <50 copies/ml by week 8, increasing to 78/87 (89.7%), and 64/66 (97%) at weeks 24 and 48, respectively. The estimated number of onwards transmissions in the first year of infection would have been 27.3 (95% credible interval: 21.7–35.3) with no intervention, 8.3 (6.4–11.2) with post‐diagnosis behaviour change only, 5.9 (4.4–7.9) with viral load reduction only and 3.1 (2.4–4.3) with both. The latter was associated with an 88.7% (83.8–91.1%) reduction in transmission. Conclusions : Disproportionate HIV transmission occurs during AHI. Diagnosis of AHI with early ART initiation can substantially reduce onwards transmission.